Metallothionein RNA levels in HL-60 cells. Effect of cadmium, differentiation, and protein kinase C activation. - Hanke, T; Tyers, M; Harley, C (1988)
Metallothionein (MT) gene transcription is regulated in a developmental and tissue-specific manner by metal ions and other agents. We examined MT expression in the human promyelocytic leukemia cell line HL-60 during differentiation along macrophage and neutrophil lineages. All HL-60 phenotypes showed similar basal levels of MT RNA with significant induction following exposure to Cd2+ but not activators of PKC. MT RNA did not correlate with growth state or with known levels of PKC activity, thus our data do not support a role for MT in HL-60 differentiation or for PKC in MT expression.